2021
DOI: 10.1007/s11606-020-06351-7
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents’ Perceptions of Morning Report: a Multicenter Survey

Abstract: BACKGROUND: Residents rate morning report (MR) as an essential educational activity. Little contemporary evidence exists to guide medical educators on the optimal content or most effective delivery strategies, particularly in the era of resident duty-hour limitations and shifts towards learnercentric pedagogy in graduate medical education. OBJECTIVE: Assess resident views about MR content and teaching strategies. DESIGN: Anonymous, online survey. PARTICIPANTS: Internal medicine residents from 10 VAaffiliated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…Literature reports have suggested that learners in the medical field have been satisfied with online learning, 3,4 and the findings of the current study support this. Most survey respondents stated that they would recommend this rotation to someone else and would participate again if given the chance.…”
Section: Discussionsupporting
confidence: 83%
“…Literature reports have suggested that learners in the medical field have been satisfied with online learning, 3,4 and the findings of the current study support this. Most survey respondents stated that they would recommend this rotation to someone else and would participate again if given the chance.…”
Section: Discussionsupporting
confidence: 83%
“…Our results have relevance for medical educators in several ways. First, our observations of attending participation in morning report align with resident expectations: in a 2021 survey of internal medicine residents, Albert et al found that residents preferred practical clinical teaching at morning report and that the top three teaching domains desired by residents were differential diagnosis, diagnostic work-up, and management [ 13 ]. These were found to be the three most prevalent categories of attending teaching comments in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Two recent surveys have helped delineate resident and program director expectations. A 2021 survey of residents at ten internal medicine programs concluded that the duration and content of attending commentary influences residents’ perceptions of morning report quality but found that only 61% of residents desired faculty attendance [ 13 ]. Similarly, a 2022 survey of internal medicine program directors found contrasting opinions on how often attending physicians should make comments during morning report, with some praising frequent teaching by faculty and others striving to maximize resident-driven education with less faculty commentary [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that many (especially junior) hospital doctors value the morning report as a cornerstone in medical education and see it as a space for learning through cases and patient handover [ 6 10 ]. In their study, Albert et al found that internal medicine residents consistently value the opportunity provided by morning reports to discuss compelling cases, practice clinical reasoning and have group discussions in a supportive learning environment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Heppe et al investigated the format and content of internal medicine morning reports in the US and found that the morning report predominantly consists of case-based presentations [ 12 ]. However, they argue that learning outcomes could be improved by implementing principles from adult learning theory, e.g., co-learning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%